Estimated 24-h urinary sodium and sodium-to-potassium ratio are predictors of kidney function decline in a population-based study. Issue 9 (September 2019) - Deriaz, Denis; Guessous, Idris; Vollenweider, Peter; Devuyst, Olivier; Burnier, Michel; Bochud, Murielle; Ponte, Belen
Abstract : Background: The prevalence of chronic kidney disease (CKD) is increasing worldwide in part due to population ageing. Identifying risk factors for age-related kidney function decline could help in understanding mechanisms for kidney ageing. Sodium and potassium intakes are associated with CKD progression in the renal population, but little is known on their role in renal function decline [mean estimated glomerular filtration rate variation (ΔeGFR)] in the general adult population. Method: We therefore explored the association of urinary sodium and potassium excretions with ΔeGFR in a longitudinal population-based cohort. We estimated 24-h urinary sodium (eUNa), potassium (eUK) and sodium-to-potassium ratio (eUNa/K) from spot urine using Kawasaki formulae. We performed multivariate linear regression models studying the association of eUNa, eUK and eUNa/K with yearly ΔeGFR, taking several covariates into account, including baseline eGFR and albuminuria. Results: There were 4141 white participants from which 54.3% were women. Median age was 51.5 [43.6–60.6] years and mean baseline eGFR 88 (SD 15) ml/min per 1.73 m 2 . During a median follow-up of 5.4 years, mean ΔeGFR was −0.59 (SD 1.68) ml/min per 1.73 m 2 per year. In the fully adjusted model, high eUNa and eUNa/K were associated with faster renal function decline with standardized coefficients β = −0.07 (95% confidence interval: −0.11 to −0.04) and β = −0.05 (95% confidence interval: −0.08 to −0.02), respectively. By contrast, eUK, taken alone, showed no association. Conclusion: These results suggest that dietary sodium and potassium intakes may play a role in kidney function decline in the general adult population. Whether lowering sodium and increasing potassium in the diet may help in CKD prevention needs further exploration. Abstract : Supplemental Digital Content is available in the text